Induction of Synthetic Polyploids of Porang (Amorphophallus muelerri Blume) and Assessment of Its Genetic Variability Using Morphological Data and RAPD Molecular Marker - Suyono, Suyono; Indivia, Imey Tamara; Resmisari, Ruri Siti; Fitriyah, Fitriyah; Wahyudi, Didik (Universitas Gadjah Mada, 2023)
This study uses morphological characteristics and RAPD markers to evaluate the polyploidization of synthetic porang. Seeds of triploid porang (2n=2x=26) were soaked in the different colchicine concentrations for 24 hours. After colchicine treatment, the porang seeds were planted to an MS medium that contained 2.2 µM of 6-benzylaminopurine (BAP), then, 40 days after planting in the MS media, the morphology and molecular of synthetic polyploid porang were characterized. For DNA extraction, a total of 100 mg of young leaves of porang plantlet was collected. One way Anova followed by the Duncan test (95%) was performed for phenotypic characterization. The number of different alleles, number of effective alleles, Shannon's information index, diversity, and unbiased diversity were assessed for genetic diversity. Synthetic polyploid porang has a higher total shoot, root, and wider leaves than normal porang. Polyploidy induction also successfully increased the genetic diversity of porang, and the genetic diversity will increase porang adaptability and sustainability of porang cultivation.